Small area estimation in the case of nonesponse - Nekrašaitė-Liegė, Vilma (Lietuvos matematikos rinkinys, 2009)
In this paper the effect of model and nonresponseadjustment on different types of estimators for the totals of small area domains is examined. The empirical results are based on Monte Carlo simulations with repeated samples drawn from a finite population constructed from the real data from the Lithuanian Business Survey.